Transcriptomic profiling of skeletal muscle in the DMD mdx rat model of Duchenne muscular dystrophy - Gorji, Abdolvahab Ebrahimpour; Kliczkowska, Katarzyna; Ollik, Marcin; Le Guiner, Caroline; Wilczak, Jacek; Bielecki, Wojciech; Ostaszewski, Piotr; Shirali, Masoud; Roudbari, Zahra; Sadkowski, Tomasz (Scientific reports, 2025)
Duchenne muscular dystrophy (DMD) is a severe X-linked recessive disorder caused by a mutation in the Dmd gene, leading to progressive muscle degradation, increasing weakness, and typically resulting in death before the third decade of life. To investigate the pathobiology of DMD, this study employed the Sprague-Dawley Dmd-mutated rat model (DMD ) and analyzed gene expression profiles and pathological molecular pathways. The methods used included histopathological, biochemical, and transcriptomic analyses of dystrophic skeletal muscle from DMD and wild-type (WT) individuals. Histological analysis of skeletal muscle tissue from DMD rats revealed multifocal necrosis, fibrosis, and inflammation, whereas WT rats displayed normal muscle architecture. Biochemical analysis revealed significant alterations in plasma markers of muscle damage and metabolism in DMD rats compared to WT controls, including elevated AST, ALT, ALP, CPK, and LDH levels. Additionally, oxidative status measurements showed reduced antioxidant capacity and increased lipid peroxidation in dystrophic skeletal muscle, as evidenced by lower TAS, GR, GPx, and SOD activities and higher TBARS levels. RNA-seq analysis identified 3,615 differentially expressed genes between the two groups, associated with muscle contraction, extracellular matrix (ECM) organization, and cytoskeleton organization. Notably, Dmd, Actc1, Col6a1, and Mmp2 were significantly downregulated. Gene ontology and pathway enrichment analyses indicated dystrophic changes in skeletal muscle, disruptions in calcium homeostasis, and alterations in actin cytoskeleton regulation. KEGG and Reactome pathway analyses revealed upregulation of the MAPK signaling and immune system pathways and downregulation of the ECM organization pathway. These findings support the hypothesis that targeting complex intracellular signaling pathways in DMD may represent a promising therapeutic strategy. Given that the DMD rat model closely mimics human DMD pathology compared to other animal models, it offers a more realistic platform for studying the molecular mechanisms of the disease and improving the translational potential of therapeutic approaches.